Maximally Disfiguring Surgery for Forefoot Osteomyelitis: Time for a Rethink?. (March 2020) - Lee, Han Jie; Chin, Ken Min; Lee, Shaun; Yap, Hao Yun; Ch'ng, Jack Kian; Chng, Siew Ping; Tay, Hsien Ts'ung
The treatment of choice for diabetic foot osteomyelitis is surgical debridement and targeted antibiotics with or without revascularization, depending on vascular status. In our society, debridement is done by either a vascular or orthopedic surgeon, and the common teaching is that generous amputation of bone with the accompanying soft tissue envelope is essential for adequate source control and to prevent recurrence (which remains as high as 30% even with this approach). Most of our patients undergo formal ray amputation through the metatarsal neck, while a few get digital amputations through the interphalangeal joints. Many of the resultant wounds cannot be closed and are left to heal by secondary intention. These amputations invariably alter the biomechanics of the foot and leave large and slow-healing open wounds, which have associated adverse psychosocial impacts. We describe 2 cases of patients who had osteomyelitis in the region of the forefoot who underwent complete bony resections of the osteomyelitis but with sparing of the soft tissue envelopes with good outcomes, and we challenge the dogma that maximal debridement of soft tissue must accompany debridement of necrotic and infected bone.